GNAI2 polymorphic variance associates with salt sensitivity of blood pressure in the Genetic Epidemiology Network of Salt Sensitivity study - Zhang, Xiaoling; Frame, Alissa A.; Williams, Jonathan S.; Wainford, Richard D. (Physiological genomics, 2018)
Salt sensitivity of blood pressure (BP) increases hypertension risk and associated adverse cardiovascular outcomes. At present, there are no validated rapid tests or diagnostic markers to identify salt sensitivity of BP in clinical practice. Based on our prior animal studies that report a role for brain Gαi 2 proteins in the salt sensitivity of BP and evidence that GNAI2 single nucleotide polymorphisms (SNPs) associate with hypertension risk, we investigated the hypothesis that GNAI2 SNPs associate with salt sensitivity of BP in humans. Our data provide the first evidence that a GNAI2 SNP ( rs10510755 ) positively associates with salt sensitivity of BP in the Genetic Epidemiology of Salt Sensitivity data set (continuous phenotype P = 0.049, case-control phenotype P = 0.039; n = 968), independently of subject sex or age. These observations suggest that genotyping at GNAI2 may be a useful biomarker in identifying individuals at risk for developing salt-sensitive BP and related complications or in identifying salt sensitivity within the hypertensive population.